Whose Islam? the western University and modern islamic thought in Indonesia - Abbas, Megan Brankley (Redwood City Stanford University Press, 2021)
Building a modern Islamic college -- McGill University as a "midwife for the Islamic reformation" -- A fusionist transformation at the Ministry of Religious Affairs -- Islam and development, Chicago-style -- The specter of academic imperialism -- Conclusion : the future of Islamic studies.
"In this book, Megan Brankley Abbas argues that the Western university has emerged as a significant space for producing Islamic knowledge and Muslim religious authority. For generations, Indonesia's foremost Muslim leaders received their educations in Middle Eastern madrasas or the archipelago's own Islamic schools. Starting in the mid-twentieth century, however, growing numbers traveled to the West to study Islam before returning home to assume positions of political and religious influence. Whose Islam? examines the far-reaching repercussions of this change for major Muslim communities as well as for Islamic studies as an academic discipline. As Abbas details, this entanglement between Western academia and Indonesian Islam has not only forged powerful new transnational networks but also disrupted prevailing modes of authority in both spheres. For Muslim intellectuals, studying Islam in Western universities provides opportunities to experiment with academic disciplines and to re-imagine the faith, but it also raises troubling questions about whether and how to protect the Islamic tradition from Western encroachment. For Western academics, these connections raise pressing ethical questions about their own roles in the global politics of development and Islamic religious reform. Drawing on extensive archival research from around the globe, Whose Islam? provides a unique perspective on the perennial tensions between insiders and outsiders in religious studies"--
Description based on publisher supplied metadata and other sources
Keywords: Islam-Indonesia-History-20th century; Electronic books